Introduction of Stereo Chemical Constraints into β -Amino Acid Residues - Chinnasamy Selvakkumar; Karthikeyan Muthusamy; Sathishkumar Chinnasamy (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Over the last 20 years, a large body of work in the literature has focused on the folded structures formed by peptide sequences containing backbone homologated residues. Currently increasing interest in peptide based vaccines for several infectious diseases, and non-infectious diseases. The work of Seebach in Zurich [1] and Gellman in Madison [2], established that oligomers of β amino acid residues can form novel helical structures in solution and in the solid state. Two distinct types of hydrogen bonded helical structures were demonstrated in these studies for oligomeric β peptides. The C12 helix which is an analog of the canonical 310 helical structure in "all α" sequences, has the same hydrogen bond directionality (C=Oi .....H-Ni+3). The second helical form, the C14 helix, has the opposite directionality (C=Oi.....H-Ni+4), which is unprecedented in α peptide sequences [3,4]. These reports sparked a flurry of activity on the conformational properties of β peptide oligomers. An early study from Appavu et al. [3-7], had demonstrated that unsubstituted β and γ amino acid residues can be incorporated into oligopeptide helices, without disturbing the overall helical fold [4].